The other Yijing the Book of changes in Chinese history, politics, and everyday life - Hon, Tze-ki 1958- (Prognostication in history, 2022)
"In imperial China, the Yijing (Book of Changes) was not just read as a Confucian classic for moral cultivation, but also put into practice to solve problems of everyday life. To explain why the Yijing was so widely used in China, this volume examines its multiple textual layers, its divinatory practices, its medical uses, and its role in Chinese modernity. Together, the ten chapters demonstrate that the Yijing is indeed a living text used by both the educated elite and the populace to alleviate their fear and anxiety. Contributors are: Andrea Bréard. Chang Chia-Feng, Constance A. Cook, Stéphane Feuillas, Tze-ki Hon, Liao Hsien-huei, William Matthews, Tao Yingna, Xing Wang, and Zhao Lu"